2012
DOI: 10.1007/s00428-012-1354-4
|View full text |Cite
|
Sign up to set email alerts
|

Guideline on the requirements of external quality assessment programs in molecular pathology

Abstract: Molecular pathology is an integral part of daily diagnostic pathology and used for classification of tumors, for prediction of prognosis and response to therapy, and to support treatment decisions. For these reasons, analyses in molecular pathology must be highly reliable and hence external quality assessment (EQA) programs are called for. Several EQA programs exist to which laboratories can subscribe, but they vary in scope, number of subscribers, and execution. The guideline presented in this paper has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(96 citation statements)
references
References 11 publications
1
95
0
Order By: Relevance
“…For predictive testing in NSCLC, reports have been published for EGFR 40–42 and KRAS 42 mutational analysis, and ALK 4344 Guidelines for standardisation of EQA schemes have recently been introduced 45…”
Section: Resultsmentioning
confidence: 99%
“…For predictive testing in NSCLC, reports have been published for EGFR 40–42 and KRAS 42 mutational analysis, and ALK 4344 Guidelines for standardisation of EQA schemes have recently been introduced 45…”
Section: Resultsmentioning
confidence: 99%
“…The results of the first round of the ESP assessment, conducted in 59 laboratories of 8 European countries, revealed that only 70% of laboratories correctly genotyped all samples 52. Three aspects of molecular testing were assessed: the percentage of neoplastic cells in the specimen, the molecular test itself and reporting, as recommended by van Krieken et al 52 109 Because the correct mutation call rate decreases in proportion to the decreasing percentage of tumour cells in a specimen, quality assurance programmes should include samples with a low tumour content 110. To this aim, artificial paraffin blocks consisting of mutation-positive colorectal cancer cells diluted in a background of mutation phase are useful 111.…”
Section: Practicementioning
confidence: 99%
“…Methods to individualise the status of a tumour include immunohistochemistry, and molecular pathology, which is generally taken to mean the analysis of nucleic acids from tissue, cells or fluids. 2 Molecular testing is therefore becoming an essential part of the work-up for many if not most patients with solid and haematological tumours. As a consequence, most hospitals with an active oncology practice require access to laboratories that provide the necessary information on the genetic make-up of a tumour from biopsy material.…”
Section: Introductionmentioning
confidence: 99%